Heparin binding proteins of buffalo bulls seminal plasma and their relationship with semen freezability - SINGH, MAHAK; GHOSH, S K; PRASAD, J K; KUMAR, ANUJ; RAMTEKE, S S; BHURE, S K (The Indian Journal of Animal Sciences, 2013)
The present study was conducted on isolation and purification of heparin binding proteins (HBPs) in buffalo bull semen and to establish relationship between level of these proteins and freezability of buffalo semen. Total 40 semen ejaculates were selected from 4 bulls on the basis of mass activity and individual progressive motility. First part of semen ejaculates was used for seminal plasma separation, second part for estimation of cholesterol content in spermatozoa and third part was processed for cryopreservation. Based upon post-thaw motility semen samples were classified into freezable (having individual progressive motility > 40%) and non-freezable (having individual progressive motility < 40%). Seminal plasma of freezable and non-freezable semen samples were pooled separately to isolate HBPs. HBPs were isolated by affinity chromatography. Electrophoretic profile of TSPPs, HBPs was assessed by SDS-PAGE. Out of 40 semen ejaculates, 27 were found freezable and 13 as non- freezable. Seminal parameters like individual progressive motility, per cent live spermatozoa, per cent acrosome intact spermatozoa and cholesterol content of spermatozoa did not differ significantly at fresh stage between freezable and non-freezable semen, however, at post-thaw stage these parameters were significantly higher in freezable as compared to non-freezable semen samples. The level of HBPs (mg/ ml) were significantly higher in non-freezable (2.18Â±0.06) compared to freezable (1.15Â±0.04) semen. A total of 9 HBPs bands in range of 10 to 170 kDa were recorded on SDS-PAGE. The results showed that higher level of HBPs in nonfreezable semen might be responsible for more cryodamage by causing more cholesterol efflux resulting in poor freezability of semen.